PROPOSAL FOR A NEW DIGITAL TACHOGRAPH REGULATION AND TACHOGRAPH SECURITY - Gnap, Jozef; Hvizdakova, Zuzana (Doprava a spoje, 2011)
This article describes proposal for a new legislative regulation on digital tachographs that amending Council Regulation (EEC) No 3821/85 on recording equipment in road transport and amending Regulation (EC) No 561/2006 of the European Parliament and the Council in road transport. Article is focused on one of the most important changes in regulation on digital tachograph - on connection of recording equipment to a global navigation satellite system, possibility of using this connection and timetable for new tachograph introduction. Second part of this article describes integration of driver cards with driving licences. The last part of this article is about future activities in the digital tachographs security.